We meet again - Pastis, Stephan (Pastis, Stephan. Timmy Failure, 2016)
Timmy Failure, founder and head detective of his own detective agency, finds himself on academic and behavioral probation. Timmy learns he must get a good grade on a nature project or face expulsion again, and that his arch nemesis, Corinna Corinna, will be his partner for the project. Meanwhile, Timmy tries to play baseball and deal with his mother's dating.